Electron beam induced circularly polarized light emission of chiral gold nanohelices - Lingstädt, Robin; Davoodi, Fatemeh; Elibol, Kenan; Taleb, Masoud; Kwon, Hyunah; Fischer, Peer; Talebi, Nahid; van Aken, Peter A. (ACS nano, 2023)
Chiral plasmonic nanostructures possess a chiroptical response orders of magnitude stronger than that of natural biomolecular systems, making them highly promising for a wide range of biochemical, medical, and physical applications. Despite extensive efforts to artificially create and tune the chiroptical properties of chiral nanostructures through compositional and geometrical modifications, a fundamental understanding of their underlying mechanisms remains limited. In this study, we present a comprehensive investigation of individual gold nanohelices by using advanced analytical electron microscopy techniques. Our results, as determined by angle-resolved cathodoluminescence polarimetry measurements, reveal a strong correlation between the circular polarization state of the emitted far-field radiation and the handedness of the chiral nanostructure in terms of both its dominant circularity and directional intensity distribution. Further analyses, including electron energy-loss measurements and numerical simulations, demonstrate that this correlation is driven by longitudinal plasmonic modes that oscillate along the helical windings, much like straight nanorods of equal strength and length. However, due to the three-dimensional shape of the structures, these longitudinal modes induce dipolar transverse modes with charge oscillations along the short axis of the helices for certain resonance energies. Their radiative decay leads to observed emission in the visible range. Our findings provide insight into the radiative properties and underlying mechanisms of chiral plasmonic nanostructures and enable their future development and application in a wide range of fields, such as nano-optics, metamaterials, molecular physics, biochemistry, and, most promising, chiral sensing via plasmonically enhanced chiral optical spectroscopy techniques.